Efficacy and Safety of Tadalafil 5 mg Administered Once Daily in Korean Men with Erectile Dysfunction: A Prospective, Multicenter Study - Kang, Dong Hyuk (The Korean Urological Association, 2010)
PURPOSE: The aim of this study was to evaluate the efficacy of a daily dose of tadalafil 5 mg as well as its safety for the cardiovascular system in men with erectile dysfunction. MATERIALS AND METHODS: This study included a total of 162 men who were administered a daily dose of tadalafil 5 mg between April and December of 2009. A total of 127 men completed the 8-week clinical trial. The International Index of Erectile Function (IIEF)-5, blood pressure, and heart rate were measured before treatment with tadalafil (V1) and 4 (V2) and 8 weeks (V3) after treatment with tadalafil. Adverse effects were assessed at V1, V2, and V3. In cases in which the International Prostate Symptom Score (IPSS) was ≥8 at V1, maximal flow rate (Qmax) and postvoid residual volume (PVR) were measured. RESULTS: The IIEF-5 values were 11.25±3.18, 14.56±3.79, and 16.91±3.56 at V1, V2, and V3, respectively, with significant improvement (V1 vs. V2, p<0.001; V1 vs. V3, p<0.001). The IPSS values were 10.59±5.56, 9.07±6.06, and 8.15±6.10 at V1, V2, and V3, respectively, and the differences were statistically significant (V1 vs. V2, p<0.001; V1 vs. V3, p<0.001). There were no significant differences in blood pressure or heart rate. Adverse effects were observed in 7 men (5.51%) at V2 and in 5 men (3.94%) at V3. CONCLUSIONS: Tadalafil 5 mg administered once-a-day may be effective in improving erectile function. Adverse effects on the cardiovascular system may be minimal. In addition, it is believed that this may also be effective in improving voiding symptoms.